(untitled) (Bangladesh Journal of Agricultural Research, 2011)
The study was conducted at the Hill Tracts Agricultural Research Station, Ramgarh during two years in 2007 and 2008 to evaluate the variability and performance of selected 11 velvet apple germplasm. A lot of variations in different parameters were observed among the trees. The age of plant varied from 7 to 25 years having tree volume 58 m3 to 428 m3. The number of fruits ranged from 42 to 674 per plant with single fruit weight 118 to 283 g. The length and diameter ranged from 6.63cm to 7.7cm and 5.73cm to 8.3cm, respectively. The maximum edible portion (68.3%) was recorded in DD RAM 011, while it was the lowest (47.6%) in DD RAM 001. The highest TSS% ranged from 7.28% to 14.9%. Highest yield per plant (103.67 kg) was observed in DD RAM 001 and it was lowest in DD RAM 008 (5.99 kg). All the parameters showed poor correlation among them. Considering the factors of weight and size, edible portion %, TSS %, taste, sweetness, and yield per plant, the line DD RAM 011 was found better than others. Keywords: Variability; performance; velvet apple; hilly areas DOI: http://dx.doi.org/10.3329/bjar.v36i2.9248 BJAR 2011; 36(2): 223-230